1963
DOI: 10.1128/jb.86.4.642-647.1963
|View full text |Cite
|
Sign up to set email alerts
|

SPONTANEOUS LYSIS AND PHAGE-CARRIER STATE IN BRUCELLA CULTURES

Abstract: Renoux, Gerard (Université de Montpellier, Montpellier, France), and Andree Suire . Spontaneous lysis and phage-carrier state in Brucella cultures. J. Bacteriol. 86: 642–647. 1963.—When broth or saline suspensions of 60 randomly chosen Brucella strains were directly poured onto plates of Albimi Agar, distinct plaques, indicative of phage activity, developed. Unselected Brucella cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1964
1964
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
(7 reference statements)
1
5
0
Order By: Relevance
“…Ostrovskaya (1961a) demonstrated phage in 126 of 197 brucella cultures but pointed out that the phages were only weakly virulent and their lytic effect could only be seen on solid media; not all the phages could be passaged. Similar phage isolations have been reported by Lazuga & Renoux (1960), Parnas (1963a), Lazuga (1962) and Renoux & Suire (1963). Renoux & Suire showed that 60 unselected brucella cultures (representing Brucella abortus, melitensis suis and intermedia) and containing cell types which gave rise to several morphologically distinct colonial types, were all naturally infected with phage.…”
Section: Brucella Phagesupporting
confidence: 83%
See 1 more Smart Citation
“…Ostrovskaya (1961a) demonstrated phage in 126 of 197 brucella cultures but pointed out that the phages were only weakly virulent and their lytic effect could only be seen on solid media; not all the phages could be passaged. Similar phage isolations have been reported by Lazuga & Renoux (1960), Parnas (1963a), Lazuga (1962) and Renoux & Suire (1963). Renoux & Suire showed that 60 unselected brucella cultures (representing Brucella abortus, melitensis suis and intermedia) and containing cell types which gave rise to several morphologically distinct colonial types, were all naturally infected with phage.…”
Section: Brucella Phagesupporting
confidence: 83%
“…abortus and melitensis were used by Aleksandrov et al (1961) and soluble immunogenic antigen, which was liberated into the medium during the log death phase of growth, by Allen (1961). Suire (1960) reported good protection in mice using Br. abortus Strain B112 plus cell-wall extracts of Br.…”
Section: Vaccinationmentioning
confidence: 99%
“…Lysozyme and glycine have been used to induce L-form production in artificial media (21,14), and it has been reported that glycine and a lysozyme-like substance from rabbit monocytes inhibited intracellular Brucella organisms (17, 18). Another possible mechanism of L-form induction is implied by studies in which a bacteriophage has been found in recently isolated B. abortus strains (15,16,19). The bacteriophage was described as weakly lytic, and it was noted that the lysogenic bacteria produced atypical colonies.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been described in several genera of bacteria, including Myxococcus spp. (7), Pseudomonas aeruginosa (5), Rhizobium trifolii (2), Brucella abortus (19), and Yersinia enterocolitica (J. M. Fowler, A. K. Sample, and R. R. Brubaker, Abstr. Annu.…”
mentioning
confidence: 99%
“…In general, the mechanisms responsible are ill defined and appear to be diverse. Proposed explanations for the phenomenon range from a lysogenic phage (19) to a derangement in the autolytic system (7). Recently, Fowler et al (Abstr.…”
mentioning
confidence: 99%